The effects of stabilized chlorine-dioxide gel in the treatment of aphthous ulcerative conditions in children - Dimanlig, Anna Maria
A test of the relative efficacy of Durafresh® (chlorine dioxide) gel (test) versus hexetidine rinse (control in the treatment of oral aphthous ulcers in children was conducted in a clinical setting. Twenty seven subjects were randomly assigned as test or control subjects under a regimen of chlorine dioxide gel and hexetidine, respectively. Metric of the test was the recorded size of the lesion; first, at the time subject patients sought treatment (base size) and, second, at recall of subject patients. the test group showed statistically significant improvement in the reduction of size of ulcerative lesions relative to the control group. Interviews further revealed marked improvement in the alleviation of acute symptoms in all test group subjects, on the other hand, reported pain symptoms at recall appointment. Test group subjects also reported acceptable palatability of chlorine dioxide gel regimen. Control subjects, on the other hand, reported stinging taste of hexetidine. The aforementioned results indicate the relatively better efficacy of chlorine dioxide gel than hexetidine rinse in the treatment of aphthous ulcerative conditions in children.
Keywords: Aphthous; Ulcers; Chlorine dioxide; Hexetidine